Perilaku Masyarakat Terhadap Pemanfaatan Akses Layanan Air Bersih Di Dusun Jenemadingi Kab Gowa - Ella Andayanie; Yuliati Yuliati; Alfina Baharuddin (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2024)
Clean Water is One of the Basic Needs for Human Life. Dug Well Water is Used by the Jenemadingi Hamlet Community as a source of clean water for daily life such as: bathing, washing clothes, kitchen activities, and bathrooms/toilets. This counseling activity took place in Je'nemadingi Hamlet which was attended by 30 residents. The methods used during the activity were lectures and discussions. At the beginning of the activity, the team conducted counseling related to well water sanitation and its impacts and how to overcome it. The method of this counseling stage was carried out through 3 stages, namely: the socialization stage, the Implementation stage. This activity includes 3 sessions, including: The first stage: Pre-test, which is given through a questionnaire, through the lecture method, questions and answers, and discussions Post-test and assessing the results of the post-test and Stage 3 monitoring and evaluation. The clean water sanitation access education program for the Community succeeded in significantly increasing the knowledge of participants. The average value increased from 19.26 in the pre-test to 21.78 in the post-test, with a p-value of 0.001 indicating a significant difference. These results confirm the effectiveness of the clean water sanitation education program